Palestine in the literary works of Prince Mohammed bin Abdul Karim Al Khattabi - boudjemaa, akram (The Algerian Historical Journal, 2026)
Prince Muhammad bin Abdul Karim Al-Khattabi was one of the most important figures in the struggle against colonialism in its various forms and colors throughout his life with the aim of liberating the Islamic world in particular and the world in general. This is why Prince Abdul Karim Al-Khattabi is a role model in immortal Islamic heroics. One of the most important issues that he defended is the Palestinian issue, which was and still is the issue of the Islamic world, and in this research paper we will try to monitor the most important positions of Prince Al-Khattabi in support of the Palestinian issue materially and morally.